Mumps Outbreak—Colorado, 2017. (4th October 2017) - Marx, Grace; Burakoff, Alexis; Hite, Donna; Ayers, Tracy; Chase, Jennifer; Miller, Karen; Barnes, Meghan; McDonald, Carol; Miller, Lisa; Albanese, Bernadette
Abstract: Background: During 2016, an unusually high number (>5, 000) of mumps cases were reported in the United States. On January 20, 2017, we identified a mumps outbreak in the Denver metropolitan area among a Marshallese community. We performed active surveillance to assess outbreak magnitude and guide implementation of control measures. Methods: On January 22, local and state health departments initiated active case surveillance by using a church-based community roster. Each household was contacted by telephone ≥3 times to identify mumps cases, according to the 2012 CDC/Council of State and Territorial Epidemiologists case definition, and risk factors (e.g., household size). Measles, mumps, and rubella (MMR) vaccination status was reviewed in the Colorado Immunization Information System (CIIS). Four church-based vaccination clinics were held to bring participants up-to-date for MMR vaccination. Targeted messaging about mumps, MMR vaccine, and vaccination clinics was distributed through social media, churches, and Marshallese-language radio. Results: Of the 21 households on the church roster, 17 were successfully contacted, 13 of which (76%) provided data for 85 persons (median household size: 6 persons; range: 5–12). Through household interviews and laboratory reporting, we identified 47 mumps cases (17 confirmed; 30 probable). Median patient age was 20 years (range: 3 months–44 years), 24 (51%) were male, and 34 (72%) reported no or unknown prior mumps vaccination and had no MMR vaccination documented in CIIS. During vaccination clinics, 118 (80%) of 148 presenting Marshallese persons were eligible for and received MMR vaccine; of those vaccinated, median age was 21 years (range: 1–55 years) and 104 (88%) had no prior MMR vaccine documentation. Conclusion: Active surveillance, facilitated through culturally appropriate communication with church leaders, helped identify cases, disseminate materials, and promote MMR vaccination. Household interviews provided timely data to define outbreak magnitude and need for urgent MMR vaccination. Disclosures: All authors: No reported disclosures. sdsdsdsd